Postural balance in patients with social anxiety disorder - Levitan, M.N. (Sociedade Brasileira de Medicina Tropical, 2011)
Body stability is controlled by the postural system and can be affected by fear and anxiety. Few studies have addressed freezing posture in psychiatric disorders. The purpose of the present study was to assess posturographic behavior in 30 patients with social anxiety disorder (SAD) and 35 without SAD during presentation of blocks of pictures with different valences. Neutral images consisted of objects taken from a catalog of pictures, negative images were mutilation pictures and anxiogenic images were related to situations regarding SAD fears. While participants were standing on a force platform, similar to a balance, displacement of the center of pressure in the mediolateral and anteroposterior directions was measured. We found that the SAD group exhibited a lower sway area and a lower velocity of sway throughout the experiment independent of the visual stimuli, in which the phobic pictures, a stimulus associated with a defense response, were unable to evoke a significantly more rigid posture than the others. We hypothesize that patients with SAD when entering in a situation of exposure, from the moment the pictures are presented, tend to move less than controls, remaining this way until the experiment ends. This discrete body manifestation can provide additional data to the characterization of SAD and its differentiation from other anxiety disorders, especially in situations regarding facing fear.